Analisis Konsep Diri Dan Kedisiplinan Belajar Siswa MAN 1 Probolinggo Terhadap Matematika - Lestari, Wahyu; Hariyanti, Firda; Mauliska, Nur (Wacana Akademika: Majalah Ilmiah Kependidikan, 2023)
Self-concept and learning discipline on student achievement play an important role, because self-concept and learning discipline can affect students' mathematical abilities. The purpose of this study is "Analysis of Student Self-Concept and Discipline Against Mathematics". This study uses a qualitative descriptive research method. This research was conducted for 2 months at MAN 1 Probolinggo. The population of this study was 665 students of MAN 1 Probolinggo. The research sample was 42 students of class XI IIS. The results showed that students' self-concept towards mathematics produced the most frequency, namely 22 people (52.4%) in the medium category, followed by the high and low categories. Student learning discipline towards mathematics in the moderate category is the highest frequency, namely 21 people (50%), followed by the high category.